Analisis Efektivitas Program Hibah Pokmas terhadap Pemberdayaan Masyarakat Desa - Madiarsih, Noeke Chrispur; Widiawati, Diah; Hartanto, Arif Dwi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
The objectives of this study are: 1) to find out how the impact of the POKMAS program on village community empowerment; and 2) to find out what are the factors that hamper the effectiveness of POKMAS in an effort to realize the empowerment of rural communities. Based on the combination of Cluster Analysis and Root Cause Anaysis methods, the POKMAS program has proven to have implications for the empowerment of rural communities as indicated through three things, namely: 1) an increase in income especially the poor; 2) the community is able to arrange village development planning and implementation; and 3) the community is able to take responsibility. However, the implementation of the program still leaves four problems, namely: 1) the limited amount of grant funds is adjusted to the needs of the village; 2) low participation of the poor and women; 3) the interests of individuals or small groups are still more dominant; and 4) limited administrative capacity. Overall, the POKMAS program has proven to have achieved village independence so it is important to hand over development to the village. This finding can be a proliferation of empowerment models that are based on the transfer of village authority.